Treatment action campaign : managing activists - Metton, Eulalie; Sieff, Grant ([London] : SAGE, 2016)
The Treatment Action Campaign (TAC) is widely regarded as one of the most successful HIV/AIDS activist organisations in the world. However, by 2008, the organisation was facing new challenges. This book examines how founder Zackie Achmat and his team prepared TAC to change and adapt its services and operations.
Originally Published in: Metton, E., & Sieff, G. (2008). Treatment Action Campaign: Managing Activists. WBS-2008-12. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Treatment Action Campaign; Organizational change -- Case studies